Overview Report from Virtual Instruction Ekhobot Campaign - California State University Channel Islands:::::: (2020)
On Friday, April 10, 2020, the Virtual Instruction Ekhobot Campaign was launched and sent to 1,803 CSU Channel Islands (CSUCI) students. The response rate of 21.4% for the Virtual Instruction Campaign is above average as compared to most campuses in the consortium. Approximately 494 students responded to the Campaign, and 76 students had a messagefailure. This message failure is quite high. An investigation is underway to see if the message failure is a function of the Campaign or due to students' phone status changing. The purpose of this Campaign was to ask students to respond to one primary question about virtual instruction to coincide with the end of CSUCI's second week of virtual instruction.